2017
DOI: 10.1097/inf.0000000000001397
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment with 10% Sinecatechins Ointment for Recurrent Anogenital Warts in an Eleven-Year-Old Child

Abstract: Treatment of anogenital warts was successful in an 11-year-old child with sinecatechins ointment 10%. After application for 10 weeks, the warts completely disappeared, without recurrence during a 12-week follow-up. Treatment was well tolerated, without notable side effects. Sinecatechins appear to be a reasonable treatment for anogenital warts in children who have difficulty tolerating painful destructive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
0
13
0
4
Order By: Relevance
“…Second, in contrast to the TID regimen recommended in adults, most of our patients were prescribed sinecatechins ointment BID, given the lack of pharmacokinetic data on sinecatechins in children and for ease of use. The use of the ointment three times daily may confer a shorter time to resolution; our study demonstrated a median time to resolution of 2.9 months, compared to reports of resolution ranging from 1 to 2.5 months when used TID . Together with the low adverse effect rate and variable compliance, this suggests a TID regimen may be more efficacious.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Second, in contrast to the TID regimen recommended in adults, most of our patients were prescribed sinecatechins ointment BID, given the lack of pharmacokinetic data on sinecatechins in children and for ease of use. The use of the ointment three times daily may confer a shorter time to resolution; our study demonstrated a median time to resolution of 2.9 months, compared to reports of resolution ranging from 1 to 2.5 months when used TID . Together with the low adverse effect rate and variable compliance, this suggests a TID regimen may be more efficacious.…”
Section: Discussionmentioning
confidence: 46%
“…Preliminary studies have similarly demonstrated efficacy for extragenital warts . The use in children has been limited, with only three reports of treatment with sinecatechins ointment in the literature to date . In two‐thirds of these cases, warts resolved completely after thrice daily use of sinecatechins ointment for 8‐10 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…This study evaluated demographic data and clinical outcomes of 37 children treated for anogenital warts with topical imiquimod and sinecatechins as a monotherapy and in combination with other commonly used treatments for AV. Though the use of sinecatechins and imiquimod has been reported in case reports in children with AV, overall efficacy and safety have not been effectively addressed in the literature . One case series with 24 children has shown a 67% efficacy using sinecatechins in preadolescent and adolescent children .…”
Section: Discussionmentioning
confidence: 99%
“…Podophyllin, a cytotoxic plant extract that disrupts microtubule formation, is also sometimes used topically in children, but systemic toxicity has been reported . Other medical treatments such as topical imiquimod or sinecatechins have been reported to be effective in several case reports . Imiquimod induces an antitumoral inflammatory response through activation of toll‐like receptor 7 and is approved for treatment of AV in adults and children age 12 years and older .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation